Sz shape side table from kelempayan wood (neolamarckia cadamba) / Hadi Shapii Ahmad Shapi'i - Ahmad Shapi'i, Hadi Shapii (Faculty of Applied Sciences, 2019)
Shortage of material supply, expensive price and heavy weight of wood for furniture production are the reasons kelempayan wood has an ability to be ,alternative to replace hardwood materials in making of low side density table. In this study, the SZ, side table was design and produce by using kelempayan wood. After SZ side table has been produced, the survey was done by distributing a set of questionnaire, online through Google form application that involved 150 respondents. The few issues have been analysed such as raw material, design, marketing and satisfaction. Based on the result, most of correspondents agreed to the factors. Based on demographic analysis, there was indicated gender, profession, and age. For descriptive analysis results shows that the mean value of 4.5 for marketing variable was the highest value for the rating score. Next, competitive analysis results show the gender indicated that male respondents get the higher mean rating than female respondents. For profession, students gave higher mean rating mostly for all factors and lastly for the age, from 18 to 23 years old gave highest values mostly for all factors. Generally, based on correlation analysis showed that the positive weak correlation value for all factors included raw material, design and marketing which did not influenced customer satisfaction.